MASALAH PSIKOSOSIAL: STRES PADA SISWA SEKOLAH ASRAMA (BOARDING SCHOOL): LITERATURE REVIEW - Nur Afifah Yusfika; Gamya Tri Utami; Reni Zulfitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Boarding school is school that has a higher demand in terms of personality development, character development, and the inculcation of life values when it compared to a non-boarding school. The many demands and activities could cause several problems for students, both physical and psychological problems. One of psychological problem that might be faced by students is stressful. This study aimed to determine the description of stress in boarding school students. The design of this research is literature review. Research article search was conducted through the electronic database Google Scholar and Semantic Scholar with keyword students stress and stress boarding school by the period of 2016- 2020. Based on 10 research articles, it was found that 2 studies showed the majority of students attending boarding school in the normal category, but 8 studies found that the majority of students had stress which shows a moderate level. Stress of students in boarding schools can be influenced by many factors. Thus, good stress management is needed to increase the value of education and decrease the impact of stress. Keywords: boarding school, stress, students